The Know-Nothings talk turkey - Spirn, Michele; Alley, R. W., (Robert W.) ([New York] : HarperCollins, 2000)
Four friends celebrate Thanksgiving in their own silly way.
School Library Journal.
Booklist.
1.9
K-3
Keywords: Thanksgiving Day -- Fiction; Turkeys -- Fiction; Friendship -- Fiction; Humorous stories; Thanksgiving Day -- Fiction; Turkeys -- Fiction; Friendship -- Fiction; Humorous fiction; Thanksgiving Day -- Fiction; Turkeys -- Fiction; Friendship -- Fiction; Humorous stories